2020
DOI: 10.1177/0081246320977759
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence and severity of depressive symptoms among undergraduate students at a South African University, 2016–2019

Abstract: University students are particularly vulnerable to mood disorders. This vulnerability may be increasing, with recent investigations reporting sharp rises in the prevalence of depression and other psychiatric disorders. Moreover, previous studies indicate that first-year undergraduates tend to show more depression and suicidal ideation than students in subsequent years. However, most studies in the extant literature emerge from high-income countries in the global north; relatively few focus on university studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…These findings corroborate Laher et al (2021) who note that psychosocial challenges significantly restrict social adjustment in higher education institutions, hinder academic attainment, and can be linked to increases in suicides when people fail to cope with such pressures. The unique setting of rural institutions puts such institutions at more significant risk because they usually do not have sufficient resources to help students cope (Pillay et al, 2020;Rousseau et al, 2021).…”
Section: Figure 3 Interpersonal Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings corroborate Laher et al (2021) who note that psychosocial challenges significantly restrict social adjustment in higher education institutions, hinder academic attainment, and can be linked to increases in suicides when people fail to cope with such pressures. The unique setting of rural institutions puts such institutions at more significant risk because they usually do not have sufficient resources to help students cope (Pillay et al, 2020;Rousseau et al, 2021).…”
Section: Figure 3 Interpersonal Relationshipsmentioning
confidence: 99%
“…In South African universities, psychosocial wellness has recently become embedded in the pressing public health issues owing to unprecedented incidents of attempted suicide and suicide occurrence in the country (Makhubela, 2021;van Zyl et al, 2017). These concerns are more pronounced in rural universities which in most instances have very limited resources for students and staff to cope amid the academic pressures extant in universities (Pillay et al, 2020;Rousseau et al, 2021). Psychosocial challenges significantly impede social adjustment to university and academic attainment and is linked to increased suicidality (Laher et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mental disorders, especially depression and anxiety, affect a significant proportion of the South African population, forming an upward trend that is expected to increase ( Van der Walt et al, 2020 ; Rousseau et al, 2021 ). South Africa is categorized as an upper-middle income country ( Evans-Lacko et al, 2018 ; Scorza et al, 2018 ), characterized by many social ills, including poverty, income inequality and high unemployment, which affect the mental health of its citizens.…”
Section: Introductionmentioning
confidence: 99%
“…A recent South African study of students (mean age 18.9 years) at two universities in large metropolitan areas noted a 12-month prevalence for suicide ideation of 40.9%, with women and Black students at increased risk (Bantjes et al, 2021). Another South African investigation found that 'severe' depressive symptoms using the Beck Depression Inventory increased from 3.81% in 2016 to 12.63% in 2019 (Rousseau et al, 2021).…”
mentioning
confidence: 99%